Good or Bad Robots? Responsible Robo-Advising - Salo-Lahti, Marika (Kluwer Law International, 2022)
FinTech has changed the way financial services are produced and delivered.1 As the Digital Finance Strategy for the EU put it: the future of finance is digital. Digital finance has also helped people and businesses tackle the unprecedented challenges caused by the COVID-19 pandemic. We increasingly rely on digital and remote technologies. The role of regulation is to make sure that these technologies are used in a responsible way.2 Robo-advising is one of the innovations relating to FinTech. This article addresses central challenges and risks in robo-advising, and the regulatory means to tackle them. When these challenges are resolved, robo-advising can provide customers with an easy-to-use, cost-effective and flexible service.
Keywords: Algorithm; Cybersecurity; financial literacy; FinTech; information security; Investment advising; legal design; MiFID II; Responsibility; Robo-advising; fi=Talousoikeus|en=Business Law|